Theory and measurement of low-frequency structure-borne sound in concrete buildings - Cheng, Jiali (My University, 2024)
Low-frequency structure-borne sound is a critical issue because this type of noise travels long distances with little attenuation. This has become a growing concern with the advancement of audio technology and loudspeakers. It is especially problematic in spaces like home theatres and concert halls, where it can cause discomfort and long-term health effects for residents, even those located at a distance. Therefore, predicting effective sound insulation in the early building design process is essential. This thesis investigates the behaviour of low-frequency vibrations in a concrete floor within an office building, focusing on the relationship between the propagation speed of bending waves, the loss factor, and the attenuation of vibrations over distance. It is built on the work of Østvik1, who described the correlation between structural reverberation and distance-dependent damping of vibrations of a concrete slab within a building. A theoretical model of vibration decay, based on the propagation speed and the loss factor of the structure, was proposed and validated through vibration measurements. These measurements were conducted at multiple excitation points on both the floor and the wall, with results confirming that the propagation speed of bending waves follows the expected square-root dependence on frequency. A lower propagation speed was observed when the floor was excited on the wall, compared to direct excitations on the floor. The level decay predicted by the model generally followed a logarithmic pattern, with geometric spreading being dominant. More significant decay was observed at higher frequencies than at lower ones. Furthermore, the structural reverberation time was found to decrease with increasing frequency, indicating that the vibrations last longer at low frequencies. The total loss factor also decreased with increasing frequency, suggesting that energy loss per oscillation is greater at low frequencies. These findings provide valuable insights into lowfrequency vibration propagation. Further research with additional excitation and measurement positions is needed to validate the proposed relationship and better understand the variations observed in this study.
Keywords: Low-frequency sound, structure-borne sound, concrete, structural analysis, bending waves, time delay, level decay, distance attenuation, structural reverberation time, loss factor